1993
DOI: 10.1007/bf01308615
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal dysfunction and delayed colonic transit in patients with progressive systemic sclerosis

Abstract: We studied 14 unselected patients with progressive systemic sclerosis (PSS), six with constipation, and eight with normal bowel habits. A control group, matched for age and sex, comprised six patients with idiopathic constipation and seven healthy subjects. Anorectal manometry was performed with perfused catheters and segmental colonic transit was measured by a radiopaque marker technique. The resting pressure of the anal canal was significantly reduced in PSS with constipation (P < 0.05). The rectoanal inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 19 publications
5
18
0
3
Order By: Relevance
“…In the later phases of SSc, decreases in resting pressures of the internal and external anal sphincters, decreased length of the anal canal, decreased maximum squeeze pressure, and finally, decreased rectal compliance due to collagen deposition occur (4, 106,107,110,111). The only changes that correlate with symptoms are decreased squeeze pressures (106) and decreased rectal compliance (107), which correlate with diarrhea.…”
Section: The Colonmentioning
confidence: 99%
See 1 more Smart Citation
“…In the later phases of SSc, decreases in resting pressures of the internal and external anal sphincters, decreased length of the anal canal, decreased maximum squeeze pressure, and finally, decreased rectal compliance due to collagen deposition occur (4, 106,107,110,111). The only changes that correlate with symptoms are decreased squeeze pressures (106) and decreased rectal compliance (107), which correlate with diarrhea.…”
Section: The Colonmentioning
confidence: 99%
“…The only changes that correlate with symptoms are decreased squeeze pressures (106) and decreased rectal compliance (107), which correlate with diarrhea. Presence of a rectal prolapse further decreases anal sphincter pressures and can contribute to incontinence (1 10,111).…”
Section: The Colonmentioning
confidence: 99%
“…This is abnormal in patients with Hirschsprung's disease, scleroderma, or Chagas' disease. 16,17 Rectal sensation is measured by filling the balloon in the rectum with increasing amounts of water or air and recording the volume at which the patient first feels the balloon and at the point of maximal tolerated volume. Poor rectal sensation is seen in patients whose volume at first sensation and maximal tolerated volumes are high.…”
Section: Anorectal Manometrymentioning
confidence: 99%
“…8 Resting pressures in the anal canal were reported to be significantly less than in controls only in the subgroup with constipation, though results suggested that there was a trend towards abnormality in the asymptomatic SSc group.…”
Section: Discussionmentioning
confidence: 92%